2015
DOI: 10.1111/ijfs.12808
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of carrot sensory crispness with acoustic signal characteristics

Abstract: Summary The purpose of this study was to investigate the relationships of carrot sensory crispness with acoustic signal characteristics and microstructure after storage under common shelf conditions. The results showed that carrot sensory crispness declined significantly after the 14th day of storage, and the sensory score reduction was nearly up to 42% after the 28th day of storage. The carrot sensory crispness was positively related to both the waveform index (r = 0.785, P < 0.01) and sound intensity (r = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 31 publications
(41 reference statements)
5
26
2
Order By: Relevance
“…Samples were put into a self‐made collection platform and a modified stepping motor with a force of 5N was used to knock the middle part of samples. The collection method was consistent with the previous research (Liu et al, ). The acoustical signal acquisition system was shown in Figure .…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Samples were put into a self‐made collection platform and a modified stepping motor with a force of 5N was used to knock the middle part of samples. The collection method was consistent with the previous research (Liu et al, ). The acoustical signal acquisition system was shown in Figure .…”
Section: Methodssupporting
confidence: 68%
“…Based on the time‐frequency analysis theory, acoustical signals were collected by knocking sweet potatoes and denoised via Wavelet transform method according to previous work (Liu et al, , ). The equations of waveform index and acoustic energy were listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Carrot ( Daucus carota L.), one of the most popular root vegetables grown throughout the whole world which is rich in bioactive compounds like carotenoids, vitamins, and minerals (Liu et al, ; Mestry, Mujumdar, & Thorat, ). It has significant health promoting properties such as antioxidant, anti‐inflammatory, anti‐cancer, and being a precursor of Vitamin A (Garcia‐Herrera et al, ; Sharma, Karki, Thakur, & Attri, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this might be the loss of the fibrous material between the cell walls. Liu et al () observed the microstructures of carrots with a scanning electron microscope within the storage period from 0 to 28 days, and found that with the prolonged storage the crispness of the carrots declined significantly, and rupture occurred. Another study revealed that the cell wall size, thickness, and cavities of the microstructures of squeeze crisp breads were proportional to its crispness (Gondek et al, ).…”
Section: Introductionmentioning
confidence: 99%